The ethical and legal considerations on abuse of remunerative work outside public service (RWOPS) by state-employed doctors - Kwinda, Munyadziwa A (My University, 2016)
Remunerative Work outside Public Service (RWOPS), although well legislated for in South Africa, lends itself to significant abuse by state-employed doctors. The abuse of RWOPS is a reflection of the failure of the state to regulate this practice, and, as the employer, to fulfil its obligations as regards distributive justice and the provision of health care services by regulating this practice. This is both legally and ethically unacceptable. The failure of the state to use the provisions of the Public Service Act No.103 of 1994 to regulate RWOPS and deal with the breach of employment contracts by doctors who abuse this practice is illegal. Doctors who abuse RWOPS lack altruism which is central to the social contract that exists between the medical profession and society. Such doctors are devoid of trustworthiness and integrity which are core virtues in the medical profession. The abuse of RWOPS primarily has an impact on the equitable access to health services, the quality of health care received by state patients and the efficient use of health resources. This abuse of RWOPS is clearly unethical. Accordingly, this report recommends that the Department of Health applies the provisions of the law and also reports doctors who abuse RWOPS to the HPCSA so that disciplinary action can be instituted against these unethical doctors. Moreover, the South African Medical Association should guide their members to understand the obligations they have towards their employer and their patients and to refrain from advocating for unethical doctors involved in illegal practices.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, In partial fulfilment of the requirements for the degree of Master of Science in Medicine, Bioethics and Health Law Johannesburg, October 2016